Combining shock barometry with numerical modeling: Insights into complex crater formation—The example of the Siljan impact structure (Sweden). (2nd October 2017) - Holm‐Alwmark, Sanna; Rae, Auriol S. P.; Ferrière, Ludovic; Alwmark, Carl; Collins, Gareth S.
Abstract: Siljan, central Sweden, is the largest known impact structure in Europe. It was formed at about 380 Ma, in the late Devonian period. The structure has been heavily eroded to a level originally located underneath the crater floor, and to date, important questions about the original size and morphology of Siljan remain unanswered. Here we present the results of a shock barometry study of quartz‐bearing surface and drill core samples combined with numerical modeling using iSALE. The investigated 13 bedrock granitoid samples show that the recorded shock pressure decreases with increasing depth from 15 to 20 GPa near the (present) surface, to 10–15 GPa at 600 m depth. A best‐fit model that is consistent with observational constraints relating to the present size of the structure, the location of the downfaulted sediments, and the observed surface and vertical shock barometry profiles is presented. The best‐fit model results in a final crater (rim‐to‐rim) diameter of ~65 km. According to our simulations, the original Siljan impact structure would have been a peak‐ring crater. Siljan was formed in a mixed target of Paleozoic sedimentary rocks overlaying crystalline basement. Our modeling suggests that, at the time of impact, the sedimentary sequence was approximately 3 km thick. Since then, there has been around 4 km of erosion of the structure.